Unmasking the coloniality of science: towards resilient and inclusive agri-food systems - Adam, Rahma; Arulingam, Indika; Karki, Darshan; Menon, Purnima; Nchanji, Eileen Bogweh; Nortje, Karen; Osei-Amponsah, Chariy (CGIAR GENDER Impact Platform, 2023)
In this panel we reflect on the coloniality of science as a way of building more resilient, sustainable and inclusive agri-food systems. We start this interrogation from our own professional standpoint. The One CGIAR we know today aims to address food security, whilst also ensuring sustainable, natural resources management and inclusivity. Yet the foundations of the CGIAR began in the 1950s as a techno-scientific project leading to the Green Revolution. The climate crisis, environmental degradation, farmer suicides, growing food insecurity and dependency and the pervasive under- and malnutrition in many countries are argued as the outcome of agricultural developmental models imagined in the north and imposed globally through various political and economic measures. What we call “science” denies the plurality of knowledges and local contexts that may help us to manage food systems more sustainably. Similarly, what we label “technical” knowledge is often dismissive of historical indigenous knowledge about flora and fauna, which has been systematically erased as part of development projects. This panel brings together CGIAR and external researchers to discuss how food systems science is colonized and deeply subjective, and present (proposed) case studies of approaches to decolonize science: decolonizing traditional dietary approaches: Purnima Menon (Asia); hybrid water laws: Barbara Van Koppen and Inga Jacobs-Mata (Africa); and food security and sovereignty: Jahi Chappell. Our aim is to enable reflection on alternative ways of knowing and doing science.